Production of Betacyanins in Transgenic Nicotiana tabacum Increases Tolerance to Salinity - Zhou, Yanfei; Karl, Tanja; Lewis, David H.; McGhie, Tony K.; Arathoon, Steve; Davies, Kevin M.; Ryan, Ken G.; Gould, Kevin S.; Schwinn, Kathy E. (Frontiers in Plant Science, 2021)
Although red betalain pigments (betacyanins) have been associated with salinity tolerance in some halophytes like Disphyma australe, efforts to determine whether they have a causal role and the underlying mechanisms have been hampered by a lack of a model system. To address this, we engineered betalain-producing Nicotiana tabacum, by the introduction of three betalain biosynthetic genes. The plants were violet-red due to the accumulation of three betacyanins: betanin, isobetanin and betanidin. Under salt stress, betacyanic seedlings had increased survivability and leaves of mature plants had higher photochemical quantum yields of photosystem II (Fv/Fm) and faster photosynthetic recovery after saturating light treatment. Under salt stress, compared to controls betacyanic leaf discs had no loss of carotenoids, a slower rate of chlorophyll degradation, and higher Fv/Fm values. Furthermore, simulation of betacyanin pigmentation by using a red filter cover improved Fv/Fm value of green tissue under salt stress. Our results confirm a direct causal role of betacyanins in plant salinity tolerance and indicate a key mechanism is photoprotection. A role in delaying leaf senescence was also indicated, and the enhanced antioxidant capability of the betacyanic leaves suggested a potential contribution to scavenging reactive oxygen species. The study can inform the development of novel biotechnological approaches to improving agricultural productivity in saline-affected areas.